Analysis of the Factors Influencing Credit Distribution at PT. Bank BTN (Persero) Tbk. Medan Branch Office - Mulya Rafika; Christine Herawati Limbong; Eva Fitria; Nova Jayanti Harahap; Yona Melia (PT Mattawang Mediatama Solution, 2023)
The formulation of the problem in this study is how to influence Third Party Funds (DPK), Return on Assets (ROA) and interest rates on lending at PT. Bank BTN (Persero) Tbk. Medan Branch Office. While the objective of this research is to analyze the effect of third party funds (DPK), Return on Assets (ROA) and interest rates on lending at PT. Bank BTN (Persero) Tbk. Medan Branch Office either partially or simultaneously. The data source in this study is the 2012-2016 financial reports. The data analysis technique used was multiple linear regression using the SPSS version 17.0 program. The results showed that the t-count value for the DPK variable (X1) (13.112) > (12.706) or (0.048) < (0.05), partially DPK has a positive and significant effect on LDR. The t-count value for the variable ROA (X2) (11.659) < (12.706) or (0.054) > (0.05), partially ROA has no positive and significant effect on LDR. The t-count value for the variable interest rate (X3) (13.152) > (12.706) or (0.048) < (0.05), partially the interest rate has a positive and significant effect on LDR. Simultaneously the DPK, ROA and interest rate variables have a significant effect on LDR at PT. State Savings Bank (Persero) Tbk. Medan Branch (Fcount > Ftable (75.504 > 19.16) or sig F <5% (0.084 > 0.05).